Ribosomal DNA in diploid and polyploid Setaria (Poaceae) species: number and distribution - Nani, Thaís Furtado (2015)
Setaria Beauvois, 1812 is a genus of economically important forage species, including Setaria italica (Linnaeus, 1753) Beauvois, 1812 and Setaria viridis (Linnaeus, 1753) Beauvois, 1812, closely related species and considered as model systems for studies of C4 plants. However, complications and uncertainties related to taxonomy of other species of the genus are frequent due to the existence of numerous synonyms for the same species or multiple species with the same name, and overlapping of morphological characteristics. Cytogenetic studies in Setaria can be useful for taxonomic and evolutionary studies as well as for applications in breeding. Thus, this study is aimed at locating 45S and 5S rDNA sites through fluorescent in situ hybridization (FISH) in S. italica, S. viridis and Setaria sphacelata (Schumacher, 1827) Stapf, Hubbard, Moss, 1929 cultivars (cvs.) Narok and Nandi. S. italica and S. viridis have 18 chromosomes with karyotype formulas 6m + 3sm and 9m, respectively. The location of 45S and 5S rDNA for these species was in different chromosome pairs among the evaluated species. S. viridis presented a more symmetrical karyotype, strengthening the ancestral relationship with S. italica. S. sphacelata cvs. Narok and Nandi have 36 chromosomes, and karyotype formulas 11m+7sm and 16m+2sm, respectively. The 45S rDNA signals for both cultivars were also observed in distinct chromosome pairs; however chromosomes bearing 5S rDNA are conserved. Karyotypic variations found among the studied species are evidence of chromosomal rearrangements.